PENGARUH KARAKTERISTIK PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN TRIPLE BOTTOM LINE DI INDONESIA - Karyo Nugroho, Adhy; Purwanto, Agus (Diponegoro Journal of Accounting, 2013)
This study aimed to analyze the effect of firm characteristics, ownership structure, corporate governance disclosure on the triple bottom line in Indonesia. Disclosure of the triple bottom line concept is defined as a result of the company's accounts reflect overall company performance both from the economic, social, and environmental. This study uses nine variables that predicted disclosure could affect the company's triple bottom line. Four variables are indicators of the characteristics of companies that leverage, profitability, liquidity, and industry types. Furthermore, there are three variables that are indicators of the ownership structure of the company is management ownership, foreign ownership, and institutional ownership. Meanwhile, two other variables show indicators of good corporate governance and the size of the board audit committee.This study used a sample of manufacturing firms listed Indonesia Stock Exchange during the period 2008-2011. A total of 200 annual reports of companies that meet the criteria have complete data for the study expressed as a sample. This study uses quantitative and analytical methods used is multiple regression.The results showed that not all of the variables in this study significantly influence the disclosure of the triple bottom line. Only the leverage variable, type of industry, size of board of directors, and audit committees that significantly influence the disclosure by the triple bottom line of the company. Other factors examined in this study such as profitability, liquidity, institutional ownership, management ownership, and foreign ownership does not significantly influence the triple bottom line disclosure by companies.